The Impact of Osteopontin Gene Variations on Multiple Sclerosis Development and Progression. (11th September 2012) - Comi, Cristoforo; Cappellano, Giuseppe; Chiocchetti, Annalisa; Orilieri, Elisabetta; Buttini, Sara; Ghezzi, Laura; Galimberti, Daniela; Guerini, Franca; Barizzone, Nadia; Perla, Franco; Leone, Maurizio; D'Alfonso, Sandra; et al.
Abstract : Osteopontin is a proinflammatory molecule, modulating TH1 and TH17 responses. Several reports suggest its involvement in multiple sclerosis (MS) pathogenesis. We previously reported that OPN gene variations at the 3′ end are a predisposing factor for MS development and evolution. In this paper, we extended our analysis to a gene variation at the 5′ end on the - 156 G > GG single nucleotide polymorphism (SNP) and replicated our previous findings at the 3′ end on the + 1239 A > C SNP. We found that only + 1239 A > C SNP displayed a statistically significant association with MS development, but both + 1239 A > C and - 156 G > GG had an influence on MS progression, since patients homozygous for both +1239A and −156GG alleles displayed slower progression of disability and slower switch to secondary progression than those carrying +1239C and/or −156G and those homozygous for +1239A only. Moreover, patients homozygous for +1239A also displayed a significantly lower relapse rate than those carrying +1239C, which is in line with the established role of OPN in MS relapses.